Analisis Fraud Hexagon Dalam Mendeteksi Potensi Kecurangan Laporan Keuangan Pada Perusahaan Badan Usaha Milik Negara (BUMN) - Atika Gando Suri; Annisaa Rahman (Syntax Corporation, 2023)
This study aims to obtain empirical evidence of the influence of variables in Fraud Hexagon Theory that can detect financial statement fraud. This study uses the Fraud Score Model with case studies on State-Owned Enterprises (BUMN) in 2016 – 2020. The population in this study is all state-owned companies listed on the IDX in 2016-2020 which are accessed through the idx.co.id website. The sample data used in this study was as many as 13 state-owned companies. Sampling is carried out based on the purposive sampling method. The dependent variable used in this study is financial statement fraud. The independent variables used by this study are stimulus, opportunity, capability, rationalization, ego and collusion. Data analysis in this study used multiple linear regression analysis with SPSS test tool Version 26. Based on the results of the analysis, it shows that stimulus has a significant effect on financial statement fraud, while opportunity, capability, rationalization, ego and collusion do not have a significant effect on financial statement fraud.